The Production of Space and Ecological Conflict in the Novel Perempuan yang Menunggu di Lorong Menuju Laut: Study of Lefebvre and Ecocriticism - Aswati Asri; Nur Hasbi; Ayu Anriani Alle (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study aims to uncover the production of space and ecological conflict in the novel through the perspectives of space production and ecocriticism. The study uses a qualitative approach with a descriptive-interpretive design. The data source is the novel entitled Perempuan yang Tunggu di Lorong Menuju Laut by Dian Purnomo. The data consists of narrative excerpts, dialogues, and events that represent the space of Sangihe, roads, sea, land, houses, mines, officials, and community resistance. Data were collected through reading and note-taking techniques and analyzed based on the concepts of spatial practice, spatial representation, representational space, and human relations with the environment. The main instrument of the study was the researcher herself as a human instrument, assisted by data analysis guidelines. Data analysis was carried out through the stages of data reduction, data classification, interpretation, and drawing conclusions. Data validity was maintained through diligent reading, source triangulation, and theory triangulation. The results of the study indicate that Sangihe is represented as a living space produced through the work, memory, solidarity, and ecological ties of the community. In contrast, mining companies represent this space as an area of investment, concession, and exploitation. The ecological conflict in the novel is not only the threat of environmental damage, but also a spatial conflict between the living space of society and extractive capital. The implications of the findings of this study indicate that literature has an important position as a space for criticism of extractive practices and ecological injustice, and also shows how power relations work through the production of space and control of people's living areas, so that reading literature does not stop at the exploitation of nature or the resistance of characters, but also at the spatial mechanisms that enable domination and resistance to take place.